Copper catalysis with redox-active ligands - Das, Agnideep; Ren, Yufeng; Hessin, Cheriehan; Desage-El Murr, Marine (Beilstein Journal of Organic Chemistry, 2020)
Copper catalysis finds applications in various synthetic fields by utilizing the ability of copper to sustain mono- and bielectronic elementary steps. Further to the development of well-defined copper complexes with classical ligands such as phosphines and N-heterocyclic carbenes, a new and fast-expanding area of research is exploring the possibility of a complementing metal-centered reactivity with electronic participation by the coordination sphere. To achieve this electronic flexibility, redox-active ligands can be used to engage in a fruitful “electronic dialogue” with the metal center, and provide additional venues for electron transfer. This review aims to present the latest results in the area of copper-based cooperative catalysis with redox-active ligands.
Keywords: bioinspired catalysis; biomimetic copper complexes; cooperative catalysis; redox-active ligands; redox catalysis